(untitled) (REMUNOM, 2024)
ABSTRACT The present study aims to understand the relationship between social movements in public policies present in the Residents’ Association of the Quilombola Rural community of Areias de Verão, Vila Teimosa and Sussuarana, in the municipality of Livramento-PB, through identification, knowledge, and applicability of the social movement. With the following specific objectives: the importance of the social movement for the Livramentense community; identify the social and political dimension of the movement; and finally, analyze the social movement as a tool for understanding society’s needs. From the perspective of nature, the research is exploratory, as it seeks greater knowledge of the topic to be studied, making it visible, flexible and adaptable to changes, as well as descriptive, since it carries out data collection, through standardized collection techniques, such as forms and questionnaires, for example. Having said that, this course conclusion work aims to provide an overview of public policies and implementation in the quilombola community present in the municipality of Livramento-PB, aiming at the implementation and construction with popular participation of all rights guaranteed by law.